Penguatan Motivasi Belajar Dan Kemampuan Berpikir Kritis Siswa SMP Melalui Media Interaktif Quartet Cardgame Terintegrasi Augmented Reality Pada Materi Sejarah Ilmuwan Muslim - Ramadhan, Mochammad Rizal; Faizin, Nur; Najib Fahmi, M. Iqbal; Mutiara Hasanah, Samudra; Khoirunnisa, Tsania (IAI Darussalam, 2023)
Learning motivation and critical thinking skills in studying history, especially Islamic history, have received less attention. Even though this is one of the indicators in realizing superior students who are faithful, intelligent, and skilled. The teacher's efforts in using media in PAI learning are also not optimal. The media used by the teacher is less effective because the media is still conventional. This is very challenging where learning media is an aspect of students that plays a major role in understanding the material. The historical material for the growth of knowledge during the Abbasid dynasty is one of the most important PAI materials for students to learn. During the Abbasid dynasty, Islam reached its limits in several fields, one of which was science. The importance of Islamic history material being studied by students made researchers implement learning media in the form of quartet cards (quartet card game). The method used in implementing the media consists of several stages, namely: 1) observation, 2) implementation of activities including: presentation of material and assistance to students, and (3) stages of activity evaluation. The quartet card game that is applied in learning is a quartet card game that is connected to an Augmented Reality-based application containing historical material about Muslim scientists. Based on the results of implementation in schools in the city of Surabaya, students feel more motivated to study Islamic history and their critical thinking skills increase after using the media quartet card game.